The hedgehog effect executive coaching and the secrets of building high performance teams - Kets de Vries, Manfred F. R. (Jossey-Bass, 2011)
"In today's global world organizations rely more and more on virtual teams. In his latest book on group coaching for high-performance teams, Manfred Kets de Vries provides a clear understanding of how to coach groups of managers and make them effective teams that can bring greatly improved performance for their companies. Executives, consultants, and coaches will learn what factors drive their success or failure and how to improve their ability to adapt to changing situations"--